Early weaning and creep feeding calves in drylot - K. Kimple; M. McKee; G. Fink; K. Conway (Kansas Agricultural Experiment Station Research Reports, 1977)
Performances of 125 commercial Hereford-cross and percentage Simmental calves were evaluated by comparing early weaning at 50 days of age (+25), nursing calves receiving a creep in drylot, and calves nursing in drylot without creep. Both a starter and growing creep were tested. Early weaned calves gained more (261 lbs., 299 lbs.) than either creep fed (251 lbs., 277 lbs.) or noncreep fed (107 lbs., 125 lbs.) calves during the 107-day trial. The best combined energy efficiency of dam and calf was for the early weaned group, and dams of early weaned calves began cycling sooner in the breeding season.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Weaning; Creep feeding; Drylot